Zoneamento ambiental e planejamento de bacias hidrográficas : estudo de caso - do local (Arroio Barracão, no município de Bento Gonçalves/RS) ao regional (região metropolitana da Serra Gaúcha) - Cobalchini, Magda Susana Ranzi (My University, 2017)
The increasing urbanization of cities has caused environmental deterioration and has damaged many watercourses that supply the population. The importance of this theme lies in demonstrating that cities are growing rapidly, without adequate planning, deteriorating watersheds with incompatible uses, and that although there is a great deal of knowledge about the global problem of scarcity of water resources, which, even protected by advanced Brazilian laws, In the environmental issue, we end up repeating opportunistic attitudes that prevail over environmental issues. This situation occurs at the local level, of a single city, crossing the horizons of the territory and goes to meet other neighboring cities, which for the same reason of an accelerated process of growth create an axis of conurbation merging territories and having among themselves common problems that Should be resolved on a regional scale. It is necessary to apply legal instruments of effective implementation such as the Environmental Zoning that recognizes the value of each part of the territory by giving it a correct and planned use aimed at the sustainability of an entire region. Chapter 1 leads us to a reflection On the construction of cities and their fragmented spaces far from the acclaimed flag of sustainability. Chapter 2 tells us about the local case study that emerges in the Urban Microbacia of Arroio Barracão, in the municipality of Bento Gonçalves, narrating its discovery as a basin And its importance as a contributor to human supply. It deals with environmental protection laws and the Master Plans that regulate land use by recognizing potentials and constraints for occupation, but that in practice the command of these areas and land use definitions is at the hand of real estate speculation generating disrespect in relation The protection of this urban hydrographic basin. It also shows that the hydrographic basins exceed the geographical limits of a municipality and what the uses of the soil located upstream of the capture, in another neighboring municipality can contribute with large negative impacts in the well. In Chapter 3 we present a survey on metropolitan regions and the question of competencies for governance. We also present a diagnosis of the current situation, through the analysis of the municipal legislations, of the 13 municipalities that compose the Metropolitan Region of Serra Gaúcha, demonstrating the urgent need for implementation Of an effective legal instrument, Environmental Zoning, for the protection of the watersheds of the entire region, thus preserving the water resources that cross the municipal frontier for every future generation.
A crescente urbanização das cidades ocasionou a deterioração ambiental e prejudicou muitos cursos de água que abastecem a população. A importância da temática reside em demonstrar que as cidades crescem rapidamente, sem planejamento adequado, deteriorando as bacias hidrográficas com usos incompatíveis e, que embora se tenha amplo conhecimento sobre a problemática mundial sobre a escassez dos recursos hídricos, que mesmo protegidos por leis brasileiras avançadas, no quesito ambiental, acaba-se por repetir atitudes oportunistas que prevalecem sobre as questões ambientais. Esta situação ocorre em nível local, de uma única cidade, perpassando os horizontes do território e vai ao encontro de outras cidades vizinhas, que pelo mesmo motivo de um acelerado processo de crescimento criam um eixo de conurbação mesclando territórios e tendo entre si problemas comuns que devem ser resolvidos em escala regional. Faz-se necessário a aplicação de instrumentos legais de implantação eficaz como é o Zoneamento Ambiental que reconhece o valor de cada parte do território atribuindo-lhe um uso correto e planejado, voltado à sustentabilidade de toda uma região. Inicia com uma reflexão sobre a construção das cidades e seus espaços fragmentados distantes da tão aclamada bandeira da sustentabilidade, reportando-se ao estudo de caso, local, que nasce na Microbacia Urbana do Arroio Barracão, no município de Bento Gonçalves, narrando sua descoberta como bacia hidrográfica e sua importância como contribuinte para abastecimento humano. Versa sobre as leis de proteção ambiental e os Planos Diretores, que regulam o uso do solo, reconhecendo potenciais e restrições para ocupação, mas que na prática o comando destas áreas e definições de uso do solo está na mão da especulação imobiliária, gerando o desrespeito em relação à proteção das microbacias hidrográficas urbanas. Demonstra também que as bacias hidrográficas ultrapassam limites geográficos de um município e o que os usos do solo situado a montante da captação, em um município vizinho, podem contribuir com impactos negativos de grandes proporções no manancial. Por fim, apresenta uma pesquisa sobre regiões metropolitanas e a questão de competências para governança, retratando o diagnóstico da situação atual, através da análise das legislações municipais dos 13 municípios que compõem a Região Metropolitana da Serra Gaúcha. Conclui pela necessidade urgente de implantação de um instrumento jurídico de alcance regional eficaz, o Zoneamento Ambiental, para planejar a proteção das bacias hidrográficas de toda a região, preservando, desta maneira, os recursos hídricos que ultrapassem fronteiras municipais, para toda geração futura.
Keywords: Zoneamento - Aspectos ambientais - Serra, Região (RS); Bacias hidrográficas; Solo - Uso; Proteção ambiental; Zoning - Environmental aspects - Brazil; Watersheds; Land use; Environmental protection